Contact- and agonist-regulated microvesiculation of human platelets - Zhang, Yanjun; Liu, Xiao; Liu, Li; Zaske, Ana-Maria; Zhou, Zhou; Fu, Yuanyuan; Yang, Xi; Conyers, Jodie L.; Li, Min; Dong, Jing-fei; Zhang, Jianning (Thrombosis and Haemostasis, 2013)
After exposure to an agonist, platelets are activated and become aggregated. They also shed membrane microparticles that participate in the pathogenesis of thrombosis, hyper-coagulation and inflammation. However, microvesiculation can potentially disrupt the integrity of platelet aggregation by shedding the membrane receptors and phosphatidylserine critical for forming and stabilising a platelet clot. We tested the hypothesis that adhesion and microvesiculation are functions of different subsets of platelets at the time of haemostasis by real-time monitoring of agonist-induced morphological changes and microvesiculation of human platelets. We identified two types of platelets that are adherent to fibrinogen: a high density bubble shape (HDBS) and low-density spread shape (LDSS). Adenosine diphosphate (ADP) predominantly induced HDBS platelets to vesiculate, whereas LDSS platelets were highly resistant to such vesiculation. Thrombin-receptor activating peptide (TRAP) stabilised platelets against microvesiculation by promoting a rapid HDBS-to-LDSS morphological transition. These activities of ADP and TRAP were reversed for platelets in suspension, independent of an engagement integrin αIIbβ 3. As the result of membrane contact, LDSS platelets inhibited the microvesiculation of HDBS platelets in response to ADP. Aspirin and clopidogrel inhibited ADP-induced microvesiculation through different mechanisms. These results suggest that platelet aggregation and microvesiculation occur in different subsets of platelets and are differently regulated by agonists, platelet-platelets and platelet-fibrinogen interactions.
Keywords: Platelets; microvesiculation; contact inhibition; anti-platelet drugs